2006
DOI: 10.1080/00049530601087504
|View full text |Cite
|
Sign up to set email alerts
|

Two principles of perception revealed by geometrical illusions

Abstract: Although perceptual illusions have been studied since the middle years of the 19th century there is no generally acceptable explanation of specific effects or of illusions in general. The central thesis proposed here is that illusions might be more fruitfully approached in terms of the principles of perception that they reveal and that apply also to normal, veridical perception. Recent experiments involving the conventional form of the Mü ller-Lyer figure presented progressively in a narrow aperture and a much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For example, the lines of an equilateral triangle in which all the angles are acute appear shorter than those of the same length in a pentagon in which all the angles are obtuse. Day (2006) extended these observations by showing that lines, also of the same length, forming a square appear intermediate in length between those of the triangle and pentagon and, moreover, that the same differences are evident in the equal dimensions of other figures . In consequence it was concluded that the apparent length of lines forming a figure is determined by the overall size of the figure of which they are integral parts.…”
Section: Critical Role Of Oblique Intersectionsmentioning
confidence: 70%
“…For example, the lines of an equilateral triangle in which all the angles are acute appear shorter than those of the same length in a pentagon in which all the angles are obtuse. Day (2006) extended these observations by showing that lines, also of the same length, forming a square appear intermediate in length between those of the triangle and pentagon and, moreover, that the same differences are evident in the equal dimensions of other figures . In consequence it was concluded that the apparent length of lines forming a figure is determined by the overall size of the figure of which they are integral parts.…”
Section: Critical Role Of Oblique Intersectionsmentioning
confidence: 70%
“…This is a striking variation on a theme by Botti ( 1906 ). (n) Another illusion by Day ( 2006 ). The half segments belonging to the cross are equal to the sides of the diamond, but appear to be longer.…”
Section: The Corpus Of Geometrical Illusionsmentioning
confidence: 99%
“…He illustrated his principle with Figures 15–19 of his panel, but there are, in my opinion, other principles at work in his examples. Day ( 2006 ) conjectured that “it is conceivable that (…) the amount of time it takes to move from one place to another is a determinant of the apparent distance between them.”—but he did not speculate on the law relating space and time.…”
Section: Measurement Theories Of Illusionsmentioning
confidence: 99%
“…Incidentally, there is evidence that the distortions in a number of illusions (Zöllner, Poggendorff and Müller-Lyer) critically depend on the presence of corner junctions (e.g. Day, 2006) and that errors on a Müller-Lyer shaft bisection task increase close to the angles (Prebedon, 2000). Thus, one of the future directions of this research will be to systematically relate the strength of this illusion to the degree of field distortion…”
Section: Discussionmentioning
confidence: 99%